Investigation of turbulent heat transfer and pressure drop characteristics in the annuli of tube-in-tube heat exchangers (horizontal lay-out) - Dirker, Jaco (University of Pretoria, 2017)
Dissertation (MEng)--University of Pretoria, 2016.